1980
DOI: 10.1161/01.cir.62.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory responses of cardiac transplant patients to graded, symptom-limited exercise.

Abstract: The electrocardiographic and ventilatory responses of 15 denervated heart patients who had undergone cardiac transplantation and 14 age-matched, normally innervated men were compared to assess the pattern of response to graded treadmill exercise. A 5-minute postexercise venous lactate sample was also obtained. Respiratory exchange ratio and ventilation (Ve) were higher in denervated patients than in normals during submaximal exercise. Peak values (normals vs denervated) for heart rate (172 vs 159 beats/min), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
6

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(61 citation statements)
references
References 13 publications
5
50
0
6
Order By: Relevance
“…HR decayed more slowly after treadmill exercise in cardiac transplant recipients than normal subjects (35), suggesting that the cardiac autonomic nerves control the recovery process of HR. In this study, CSNA returned promptly to the resting level within 1 s after the end of exercise, whereas HR decreased slowly for Ͼ30 s (Figs.…”
Section: Discussionmentioning
confidence: 95%
“…HR decayed more slowly after treadmill exercise in cardiac transplant recipients than normal subjects (35), suggesting that the cardiac autonomic nerves control the recovery process of HR. In this study, CSNA returned promptly to the resting level within 1 s after the end of exercise, whereas HR decreased slowly for Ͼ30 s (Figs.…”
Section: Discussionmentioning
confidence: 95%
“…The absence of a relationship between the hemodynamic effects and exercise capacity has been also described for other forms of heart failure therapies, including the use of vasodilators 23 , inotropic agents 24 , and heart transplantation 25 . It is believed that measurements such as functional class, 6-minute walk test, or quality of life scores may reflect physical capacity during daily activities better than ergospirometry 7 .…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that this pattern persists for 10 years following transplantation 38 . Due to posttransplantation denervation, heart rate is controlled by the humoral route dependent of the levels of catecholamines released from the suprarenal gland 9,10 . Nevertheless, submaximal heart rate remains significantly higher in transplanted patients relative to controls up to levels of 50% of maximal exercise ( fig.1) 39 .…”
mentioning
confidence: 99%